Competitive effect of dopants on magnetic and structural properties in yttrium iron garnet co-doped with Er and Cr. Issue 11 (1st August 2020) - Leal, L.R.F.; Milani, R.; Oliveira, D.M.; Guerra, Y.; Padrón-Hernández, E.; Franco, A.; Viana, Bartolomeu C.; Santos, F.E.P.; Peña-Garcia, R.
Abstract: In the present work, we have studied the competitive effect of Er and Cr dopants on the structural and magnetic properties of yttrium iron garnet (YIG) nanoparticles synthesized by the sol gel method. The YIG single phase was obtained for all samples and the variations of structural parameters were associated to the dopants influence. Fourier transform infrared spectroscopy showed typical absorption peaks of YIG, with small displacements for larger wavenumbers corresponding to vibrational modes (Fe–O) belonging to the tetrahedral sites. The behavior of the Raman vibrational modes as a function of dopant concentration confirms the insertion of Er in dodecahedral sites and Cr in the octahedral and tetrahedral sites. A frequency shifting of some Raman modes was observed as the Cr concentration increased. The powder morphology was analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), evidencing agglomerated particles with irregular shapes. The Er and Cr incorporation in YIG promote random fluctuations in the saturation magnetization, coercivity and the magnetocrystalline anisotropy constants of the synthesized compound.